2023
DOI: 10.1002/smll.202303159
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Crosslinked‐double Network PEDOT:PSS@PEGDMA toward Highly‐Efficient and Stable Tin‐Lead Perovskite Solar Cells

Abstract: Until now, poly(3,4‐ethylenedioxythiophene):poly(styrensulfonate) (PEDOT:PSS) is widely used in Sn–Pb perovskite solar cells (PSCs) due to its many advantages, including high optical transparency, suitable conductivity, superior wettability, and so on. However, the acidic and hydroscopic properties of the PSS component, as well as the incongruous energy level of the hole transport layer (HTL), may lead to unsatisfying interface properties and decreased device performance. Herein, by adding polyethylene glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…It is known that the commonly used HTL material, i.e., poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PE-DOT:PSS), is hygroscopic and corrosive, which is undesirable for the long-term stability of perovskite solar cells. 237,238 Recently, TMDs have been used as HTLs to replace the commonly used PEDOT:PSS in various kinds of perovskite solar cells to enhance charge transport and boost device performance. 239,240 For example, Huang et al reported that the exfoliated 1T-TMDs (MoS 2 or WS 2 ) nanosheets via the reaction between water and the Li-intercalated TMDs could work as the HTL in planar p-i-n perovskite solar cells.…”
Section: Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the commonly used HTL material, i.e., poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PE-DOT:PSS), is hygroscopic and corrosive, which is undesirable for the long-term stability of perovskite solar cells. 237,238 Recently, TMDs have been used as HTLs to replace the commonly used PEDOT:PSS in various kinds of perovskite solar cells to enhance charge transport and boost device performance. 239,240 For example, Huang et al reported that the exfoliated 1T-TMDs (MoS 2 or WS 2 ) nanosheets via the reaction between water and the Li-intercalated TMDs could work as the HTL in planar p-i-n perovskite solar cells.…”
Section: Photodetectorsmentioning
confidence: 99%
“…Besides DSSCs, perovskite solar cells are attracting more research attention because of the high light absorption coefficient and long carrier diffusion length of perovskites. , As the key component for charge transport and collection in perovskite solar cells, the hole transport layers (HTLs) are critical for the performance of perovskite solar cells. It is known that the commonly used HTL material, i.e ., poly­(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), is hygroscopic and corrosive, which is undesirable for the long-term stability of perovskite solar cells. , Recently, TMDs have been used as HTLs to replace the commonly used PEDOT:PSS in various kinds of perovskite solar cells to enhance charge transport and boost device performance. , For example, Huang et al reported that the exfoliated 1T-TMDs (MoS 2 or WS 2 ) nanosheets via the reaction between water and the Li-intercalated TMDs could work as the HTL in planar p-i-n perovskite solar cells . Compared to the PEDOT:PSS HTL, 1T-TMD HTL not only facilitated the charge transfer owing to its high conductivity but also provided a better band alignment with the active perovskite layer, resulting in higher power conversion efficiencies and improved long-term stability in solar cells.…”
Section: Applicationsmentioning
confidence: 99%
“…To reduce the hygroscopic property of PEDOT:PSS, Luo et al reported an approach to improve the moisture resistance by modifying the PEDOT:PSS top surface with graphene oxide to partly remove the hygroscopic PSS component. Additionally, polyethylene glycol (PEG) has been added into the PEDOT:PSS solution to reduce the protons of PSS and passivate interface defects, resulting in an improvement of the environmental stability in PEDOT:PSS-based inverted PSCs. In addition, Hu et al reported that adding soluble sodium salts (NaCl) into PEDOT:PSS solution is beneficial for improving the conductivity and hole extraction performance, resulting in a high PCE of over 18%. However, increasing the concentration of insulating NaCl can hinder the charge-transfer ability in the inverted PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…23 As a commercialized CP, the development of various stretchable and smart electronics based on PEDOT:PSS membranes has broad application prospects. 24,25…”
Section: Introductionmentioning
confidence: 99%